Neonatal COVID-19 in A Tertiary Care Hospital of Chattogram: A Case Report (Bangladesh Journal of Child Health, 2021)
Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in China in December 2019 and now has led to a global pandemic. The incidence is lower in neonates. A five days old newborn infant got admitted with history of reluctance to feeding and less movement. On admission, the newborn infant was found to be lethargic, icteric, tachypnoeic, afebrile with SPO2 of 90% throughout his hospital stay. Chest x-ray was normal but RT-PCR for COVID-19 was positive. His mother had symptoms of COVID-19 with positive RTPCR. The neonate was isolated and was treated with antibiotics along with supportive care, then improved gradually and was discharged on day 10 of his age. Suspicion about COVID-19 in newborn infants with prompt identification is essential to limit its transmission in the community.Bangladesh J Child Health 2020; VOL 44 (3) :170-173